The Use of Authentic Materials in Dveloping Students’ Writing Competence (An Experimental Study at SMA Labschool Unsyiah) - Muharri Aqly; Endang Komariah; Hendra Heriansyah (Universitas Syiah Kuala, 2017)
This study aims at examining whether the use of authentic materials as a teaching material develops students’ writing competence or not. Quantitative approach with pre-experimental study of one-group pretest-posttest design was applied in order to develop students’ writing competence in term content, grammar, mechanics, and other aspects which were acknowledged by the students as difficulties in writing learning. The population of this study was first grade students of SMA Labschool Unsyiah, while the sample was X-IPS students. The instrument used to collect the data was test which was assessed by using analytic method suggested by Brown (2007). The result of this study confirmed that the students’ scores increased after receiving the treatment. It showed that posttest scores were higher than pretest where the mean of total score of posttest is 81 while the mean of pretest is 75. Moreover, the data of both tests were analyzed by using t-test formula to find out the t-score which was gain was 4.256. Since t-score (4.256) of this study was higher than t-table (2.120), the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. The researcher concluded that using authentic materials in teaching writing develops students’ writing competence.